National seminar on Regulations and Governance Issues in India’s Seed Sector: 26-27 September 2023, New Delhi - Dadlani, Narendra; Kumar, Anjani; Spielman, David J. (International Food Policy Research Institute, 2024)
India has a very mature and vibrant seed sector with a wide network of public and private sector enterprises working closely together to make quality seeds available to farmers at affordable prices, ensuring seed security in the country. Ranked fifth in the global seed trade with a reported turnover of more than USD 6 billion, India is likely to double this figure by 2028 due to a healthy growth rate (CAGR) which is already faster than the global rate. With improved seed replacement rate (SRR) of major food security crops, better variety replacement rate (VRR) in most crops and a declining informal trade of farm saved seed (FSS), the industry is showing a strong upswing in its growth. Much of this progress can be at tributed to the continued scientific contributions of both the public and private sector which were assisted by the enabling policies of the government.